PENINGKATAN PEMAHAMAN DAN KESIAPAN AKREDITASI MELALUI WORKSHOP DI SMPIT AL ISTIQOMAH KUNINGAN - Subasman, Iman; Munawar Rosdi, Undang; Said, Usman; Robiah Adawiyah, Ade; Hamdan; Nakhma’ussolikhah (Forum Komunikasi Dosen, 2024)
SMPIT Al Istiqomah faces obstacles in meeting accreditation standards, including the low understanding of education personnel of the eight National Education Standards (SNP) and difficulties in preparing supporting documents. Assistance is carried out through intensive workshops to improve the understanding and skills of education personnel. This method includes theory, document preparation practices, and accreditation simulations. The results showed an increase in understanding of SNP from 55% to 85%, the preparation of complete supporting documents, and the readiness of the assessor visitation reached 80%. In conclusion, the workshop proved effective in improving accreditation readiness and became a replicable model for capacity building